Nickel-Catalyzed Cascade Reaction of 2-Vinylanilines with gem-Dichloroalkenes - Lin, Jin; Wu, Chaoyi; Tian, Xu (Organic letters, 2022)
An efficient nickel-catalyzed cascade reaction of 2-vinylanilines with gem-dichloroalkenes has been developed to deliver diversely substituted quinolines in good to high yields. This protocol enables effective access to quinolines bearing various functional groups in the cascade process from readily available feedstock chemicals. Mechanistic studies suggest that two plausible pathways are involved in the IPr-nickel catalytic system.